Paul van Ostaijen in beeld : Grafiek en tekeningen van tijdgenoten. - Antonis, Eric; de Nave, Francine; Buyck, Jean F; Buelens, Geert; Hellemans, Marijke; Stedelijk Prentenkabinet, Antwerpen (Antwerpen : Museum Plantin-Moretus, 1996)
Jespers, Floris ; Leonard, Jos ; Minne, Joris ; Van Straten, Henri ; Cantré, Jan Frans ; Cantré, Jozef ; Jespers, Oscar ; Joostens, Paul ; Peeters, Jozef
Antwerpen, Stedelijk Prentenkabinet, 24 februari - 2 juni 1996
kunstcatalogus